CORRELATION BETWEEN SELF-EFFICACY AND WRITING ACHIEVEMENT TO STUDENTS OF SMA ARINDA PALEMBANG - Servina Insani Simanjuntak; Gaya Tridinanti (Universitas Tridinanti Palembang, 2020)
Writing is one of the most difficult skill that foreign language learners are expected to acquire the mastery of a variety of linguistics, cognitive and sociocultural competencies. The aim of this study was to find out whether there was significant correlation or not between self-effficacy and writing achievement. The research used quantitativr mrthod by using correlation analysis . The population was the tenth grade students with the total 44 students from 2 classes of SMA Arinda Palembang. To select the sample of this study, cluster random sampling technique was implemented. There were 23 students as the sample. The data was gained from students’ self-efficacy questionnaire and their writing test. In analyzing the data, correlation analysis was used. Based on the statistical analysis, it was found that the correlation coefficient level between self-efficacy and writing achievement was 0.346 with the sig. value was higher than 0.106. In conclusion, there was no significant correlation betweeen students’ self-efficacy and writing achievement.Keywords: self-efficacy, writing achievement